Molecular mechanisms of TTC21B gene mutations in nephronophthisis type 12 and genetic prevention through PGT - Deng, Kai; Li, Jingjing; Hu, Xitao; Wei, Huijuan; Wang, Chenyi; Cheng, Qingqing; Jiang, Yu; Cai, Liyi; Tang, Di; Cao, Guiju; Wang, Xiaoyan (Frontiers in Genetics, 2025)
ObjectiveTo elucidate the pathogenic mechanism of nephronophthisis type 12 (NPHP12) caused by compound heterozygous mutations in the TTC21B gene and to implement preimplantation genetic testing (PGT) for clinical prevention.MethodsWe retrospectively analyzed the clinical data of a pediatric proband with NPHP12. The impact of the identified TTC21B mutations (c.895T>C and c.1552T>C) on pre-mRNA splicing, protein structure, and stability was assessed using bioinformatics tools. Functional validation was performed through in vitro rescue experiments in renal podocytes, quantifying effects on cellular morphology, ciliogenesis, and ciliary length. For preimplantation genetic testing (PGT), SNP haplotype analysis was employed for embryo selection.ResultsThe proband presented with renal failure and compound heterozygous TTC21B mutations (paternal c.895T>C [p.C299R] and maternal c.1552T>C [p.C518R]). Bioinformatics suggested potential splicing impacts, but minigene assays did not validate this. While c.895T>C had a minor impact on protein structure, c.1552T>C significantly altered the tertiary structure and stability. TTC21B knockdown disrupted podocyte morphology, which was fully rescued by wild-type TTC21B but only partially by either mutant. Both mutations impaired ciliogenesis and shortened ciliary length. PGT-M identified a mutation-free embryo (Embryo 1) for transfer, resulting in a healthy live birth.ConclusionThe compound heterozygous mutations c.895T>C (p.C299R) and c.1552T>C (p.C518R) in TTC21B contribute to NPHP12 by disrupting ciliogenesis and podocyte morphology. These findings provide targets for PGT-based embryo selection, successfully preventing the familial recurrence of this disease.